Effect of Administration with Bacharris Dracunculifolia on Glycemic Basal Levels in Healthy Individuals - Tauana Aparecida de Oliveira, Luiz Augusto da Silva, Renan Garcia Michel, André Luiz Snak, Ricardo Aparecido Pereira, Carlos Ricardo Maneck Malfatti, Sirval de Oliveira Neto, Andrieli Pereira Woellner, Andressa Razera Pezoti, Letícia Magri Dallastra, Guilherme Augusto Gomes Martins (Journal of Applied Pharmaceutical Science, 2013)
Some compounds found in B. dracunculifolia could be part of human diets, directly and indirectly through green propolis intake, because of their possible effect on blood glucose that could be of great relevance in the control of hyperglycemia; however, this effect has not been extensively studied. This study analyzed the effect of acute administration of B. dracunculifolia extracts on glycemic response in healthy individuals during rest. The study group consisted of eight healthy individuals at the age of 19 ± 1.3 years old, four in the treatment group (TG) and four in the control group (CG), with and without intake of 20 g/Kg of body weight of B. dracunculifolia extract, respectively. The cardiovascular parameters of blood pressure (BP) and heart rate (HR), and blood glucose (BG) were analyzed before and after treatments Statistical significance was determined using an unpaired Student's t-test and considering p
Keywords: Baccharis dracunculifolia, Blood glucose, Therapeutic agent, antidiabetic.